Pengembangan Media Pembelajaran Augmented Reality Pada Mata Pelajaran Instalasi Motor Listrik di Sekolah Menengah Kejuruan - Aswal, Muhammad; Hendri, Hendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This research discusses learning media development using Augmented Reality in the Electric Motor Installation subject at SMK Negeri 2 Sungai Full. This research aims to produce Augmented Reality learning media that is valid, practical, and effective in the Electric Motor Installation subject in class XI TITL SMK Negeri 2 Sungai Full. This type of research is research and development (Research & Development) with a 4-D model design (Define, Design, Develop, and Disseminate). The subject of this research is the Augmented Reality learning media used in the Electric Motor Installation subject. Data collection on the validity of media and materials in this research used validation sheets from two lecturers from the Department of Electrical Engineering and two teachers in the Electric Motor Installation subject at SMK Negeri 2 Sungai Full. Practicality and effectiveness testing in this research was carried out on class XI TITL students as respondents. Practicality data collection was obtained using a practicality questionnaire given to class XI TITL students as respondents who used the developed Augmented Reality learning media. The effectiveness test in this study used an objective test question sheet given to class XI TITL students to obtain effectiveness results in this study. Based on the research carried out, data obtained on the results of media validity were in the valid category, and material validation was in the valid category. The practicality test data carried out received the very practical category. The results of the effectiveness test carried out obtained the very effective category.